Clinical Forensic Medicine Advancements (International Journal of Food and Nutritional Sciences, 2022)
The area of medicine that focuses primarily on instances involving both legal and medical aspects of patient treatment is known as clinical forensic medicine. The discovery, gathering, and preservation of evidence are all parts of a forensic review. Although they are essential parts of a forensic evaluation, pattern injury recognition, injury interpretation, testimony and injury documentation (including photography), reporting requirements, and regulations are rarely discussed in training hospitals. Intricate forensic problems relating to child abuse, sexual assault, or unexpected childhood mortality are likely to be encountered by medical professionals working in prehospital care and acute care settings in their practise. This article focuses on the most recent developments in forensic evidence, shaken baby syndrome, and paediatric nonaccidental thermal injury as they apply to successful prosecution of sexual assault. Additionally, the most recent clinical forensic medicine publications from 2002 are examined. These publications incorporate useful therapeutic advice from the most insightful writings from the previous ten years.